The The Effect of Dictation Method on Students’ Writing Ability in English for Office - Frisca Andini; Dina Irmayanti Hrp (Jurnal Kewarganegaraan, 2023)
This research was aimed to investigate The Effect of Dictation Method on Students’ Writing Ability. This study was carried out at SMK PAB 2 Helvetia. The populations of this research were the students of Vocational High School grade X. The populations of this research were 115 students, but the researcher took only 79 students as the sample which divided into two parallel classes and this group namely experimental and control groups. This research took the results of the pre-test and post-text values as a determinant the effect of dictation method on writing ability in English for Office. Each class consists of 39 to 40 students. This research data was obtained after the pre-test and post-test were applied to the experimental and control groups. The data needed to test the hypothesis is taken from the test scores of each group. Based on the Mann-Whitney Test it is known mark Asymp . Sig. (2-tailed) between Post Test Classes Experiment with Class Post Test Control is 0.44, and because 0.44 0.05 then can said that Ho is rejected and Ha is accepted , or in other words: the dictation method gave a positive and significant impact on students'' writing ability in English for Office.